Synthesis and Characterization of Some New Bis-Chalconesand Their Transformation to Bis-Thiocarbamoyl-2- Pyrazoline Derivatives - Hawaiz, Farouq Emam; Hussein, Faiq Hamasaed; Azeez, Hashim Jalal (Science Journal of University of Zakho, 2013)
The starting materials alkoxy and benzyloxyacetophenones (1a-j, 2 and 3) have been prepared on the basis of Williamson synthesis of ether. The prepared and the available starting materials were reacted with terphthalaldehyde using green methods, Ultrasound , Microwave and solvent-free grinding method to give anew series of bis- chalcones (4a-s).The prepared bis- chalcones were subjected to react with thiosemicarbazide according to the Michael addition reaction to afford new biologically active bis-pyrazolinedeivatives(5a-s). The structure of the synthesized compounds were characterized  by  spectral methods: FT-IR,  1H-nmr, 13C-nmr andMass spectrometry.
Keywords: Microwave; Grinding; Chalcone; Thiosemicarbazide; Pyrazoline